Repulsive Guidance Molecule-a and Central Nervous System Diseases. (4th May 2021) - Tang, Jinhua; Zeng, Xiaopeng; Li, Hang; Ju, Lu; Feng, Jinzhou; Yang, Jun
Abstract : Repulsive guidance molecule-a (RGMa) is a member of glycosylphosphatidylinositol- (GPI-) anchored protein family, which has axon guidance function and is widely involved in the development and pathological processes of the central nervous system (CNS). On the one hand, the binding of RGMa and its receptor Neogenin can regulate axonal guidance, differentiation of neural stem cells into neurons, and the survival of these cells; on the other hand, RGMa can inhibit functional recovery of CNS by inhibiting axonal growth. A number of studies have shown that RGMa may be involved in the pathogenesis of CNS diseases, such as multiple sclerosis, neuromyelitis optica spectrum diseases, cerebral infarction, spinal cord injury, Parkinson's disease, and epilepsy. Targeting RGMa can enhance the functional recovery of CNS, so it may become a promising target for the treatment of CNS diseases. This article will comprehensively review the research progression of RGMa in various CNS diseases up to date.